Effect of CNC Lathe Machining Performance by Varying Coolant Nozzle Diameter - Zainal Ariffin, Selamat; Nor Bahiyah, Baba; Mohd, Alias; Nornajmiah, Mohamad; A. R., Yusoff; M. M., Rahman (Informatics Publishing Limited, 2016)
Background/Objectives: The cutting temperature is important in machining process. The temperature is a most common effect base on cutting parameters such as cutting speed, feed rate and depth of cut. Optimization of the cutting parameter can also reduce of heat temperature. This way can reduce cost and also can produce a good quality of production. Method/Statistical Analysis: In this study focus on effect of machining the aluminum alloy AL6061 by using a various diameter coolant nozzle during CNC lathe process of its inherent advantages. Hence, it also studies the effect of cutting temperature to the surface roughness and dimensional error that will be considered with the parameters to arrive at a conclusive result. Taguchi method orthogonal array L16’ was selected as an experimental plan for turning on AL6061 by using CNC PUMA 230 turner with carbide tool insert. The L16’ array used 5 factors and 4 levels in conduct the temperature measurement. Findings: Results show that the dominant failure mode is the surface roughness and dimensional accuracy when the nozzle orifice size increases during machining of aluminum alloy AL6061. The exploration for dimensional accuracy, productivity and the optimization of cutting speed in the technical and commercial aspects of the manufacturing processes of aluminum AL6061 are discussed in oil and gas components industries for further work. Applications/Improvements: Conclusion and recommendations will suggest an enhancement to this application.